The Interpretasi Dinamika Dan Warna Suara Pada Suite Populaire Bresilienne No. 1 Karya Villa Lobos - Mardian Bagus Prakosa (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
This research was conducted in order to formulate the interpretation of dynamics and timbre in Suite Populaire Brésilienne No.1 by Heitor Villa-Lobos. Based on the results of the pre-study, this work is one of the classical guitar’s works that has many repetitions, so that efforts to avoid the impression of monotony need to be done. The purpose of this study is to identify the structure and musical form, determine the relationship between musical structures, and interpret them through dynamics and timbre. This study uses a qualitative research type with a musicological approach. Data collection techniques were carried out by observation, interviews, and documentation studies. The results showed that Mazurka-Choro is a suite with the ABACA rondo form in which each period has a repetition. The interpretation of dynamics and timbre is generally formulated through the tonality of each period by taking into account the tempo and rhythmic patterns. Furthermore, that a general description of the dynamics and timbre through consideration of tonality, tempo, and rhythm must be complemented by an understanding of the structure of motifs and harmony. The dynamics of the melodic structure are not only interpreted according to the direction of the melodic line, but can also be interpreted the other way around based on harmony or consideration of conceptual relations between structures or concepts that are determined in order to provide a differentiator for repetition of sentences.